Acute appendicitis in adults - Vagholkar, Ketan (International Surgery Journal, 2020)
Acute appendicitis is one of the commonest abdominal emergency encountered by a general surgeon. Understanding the surgical pathology is pivotal in identifying the stage of disease at which the patient presents for better correlation of clinical features, laboratory and imaging reports. Various scoring systems enhance and aid this process. Imaging confirms the diagnosis. Early diagnosis is essential to prevent complications. Surgery is the mainstay of treatment. Appendicitis may present in various forms in different clinical settings. A uniform approach to presentations may not always yield good results. Though appendectomy is the mainstay of treatment yet a tailor made surgical plan needs to be developed after holistic evaluation of the patient. The article discusses the differential surgical approach based on the etiopathogenesis, diagnosis and variable clinical presentations.